Electric Stimulation of Neurogenesis Improves Behavioral Recovery After Focal Ischemia in Aged Rats - Balseanu, Adrian Tudor; Grigore, Monica; Pinosanu, Leonard-Radu; Slevin, Mark; Hermann, Dirk M.; Glavan, Daniela; Popa-Wagner, Aurel (Frontiers in Neuroscience, 2020)
The major aim of stroke therapies is to stimulate brain repair and to improve behavioral recuperation after cerebral ischemia. Despite remarkable advances in cell therapy for stroke, stem cell-based tissue replacement has not been achieved yet stimulating the search for alternative strategies for brain self-repair using the neurogenic zones of the brain, the dentate gyrus and the subventricular zone (SVZ). However, during aging, the potential of the hippocampus and the SVZ to generate new neuronal precursors, declines. We hypothesized that electrically stimulation of endogenous neurogenesis in aged rats could increase the odds of brain self-repair and improve behavioral recuperation after focal ischemia. Following stroke in aged animals, the rats were subjected to two sessions of electrical nonconvulsive stimulation using ear-clip electrodes, at 7- and 24 days after MCAO. Animal were sacrificed after 49 days. We report that electrical stimulation (ES) stimulation of post-stroke aged rats led to an improved functional recovery of spatial long-term memory (T-maze) but not on the rotating pole or the inclined plane, both tests requiring complex sensorimotor skills. Surprisingly, EC stimulation had a detrimental effect on the asymmetric sensorimotor deficit. Histologically, there was a robust increase in the number of doublecortin-positive cells in the dentate gyrus and SVZ of the infarcted hemisphere and the presence of a considerable number of neurons expressing tubulin beta III in the infarcted area. ES was also associated with a long-term down regulation of cortical gene expression after stroke. Among the gene that were unique to ES, we noted increases in the expression of seizure related 6 homolog like which is one of the physiological substrate of the β-secretase BACE1 involved in the pathophysiology of the Alzheimer’s disease and Igfbp3 and BDNF receptor mRNAs which has been shown to have a neuroprotective effect after cerebral ischemia.